ANALYSIS OF HUMAN RESOURCE PERFORMANCE AT HERMINA HOSPITAL SAMARINDA (IMPLEMENTASI BALANCED SCORECARD) - Andriani; Tetra Hidayati; Irwansyah (RADJA PUBLIKA, 2026)
This study aims to analyze the performance of human resources (HR) at Hermina Samarinda Hospital using the Balanced Scorecard (BSC) approach. The research method employed is a descriptive qualitative approach, with data collection techniques including interviews, observations, and documentation. The analysis is conducted based on the four perspectives of the Balanced Scorecard, namely financial, customer, internal business processes, and learning and growth. The results indicate that overall HR performance is in the “fairly good” category. The financial perspective shows good operational efficiency, the customer perspective indicates a high level of patient satisfaction, the internal business process perspective still requires improvement, and the learning and growth perspective demonstrates continuous human resource development. The Balanced Scorecard is proven to be an effective tool for comprehensive performance measurement.